Constitutive rules as a logical problem in the origin of John Rawls’ moral philosophy - Aguayo-Westwood, Pablo (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2025)
This article offers a critical review of John Rawls’s 1955 essay Two Concepts of Rules and argues that a full understanding of his mature work requires examining his early philosophical development. The central hypothesis posits that Rawls’s analysis of constitutive rules is essential for understanding the epistemic foundations of his later theory of justice. A key distinction is that drawn between justifying an action that falls within a rule (or practice) and justifying the rule itself. This distinction allowed Rawls to defend utilitarianism against its critics, highlighting their logical misunderstanding of how this theory evaluates actions. Furthermore, the article argues that Rawls’s early concern with practices and social institutions directly influenced his subsequent interest in the basic structure of society, developed in A Theory of Justice. Ultimately, it reveals Rawls’s nascent attention to the evaluation of systems of rules that shape social practices, rather than focusing solely on individual actions, representing a crucial step in the elaboration of his theory.